Employment Services South Africa usage: Perspectives from jobseekers and employees - Akhonamaqwabe Gumede; Stellah Lubinga; Tyanai Masiya; Michel Tshiyoyo (International Review of Social Sciences Research)
This paper examines the perspectives of the Department of Employment and Labour employees and jobseekers on the usage of the Employment Services South Africa (ESSA) system. The system's primary aim is to place unemployed South Africans in available job opportunities by facilitating information sharing between employers and jobseekers based on the jobseekers’ qualifications and experience. Data was collected from 34 respondents, including employees of the Department of Employment and Labour and jobseekers, through qualitative interviews. The findings revealed that many unemployed jobseekers did not effectively use the ESSA system. While the ESSA system is valued by the Department of Employment and Labour employees, its adoption, perceived usefulness, accuracy, and effectiveness among jobseekers are lacking. The system still struggles with low visibility, a lack of awareness, and trust among jobseekers, who often look elsewhere for effective recruitment.